The Educational and Fertility Effects of Sibling Deaths - Dhanushka Thamarapani; Marc Rockmore; Willa Friedman (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2018)
An emerging literature finds that childhood exposure to adverse events determines adult outcomes and behavior. We extend this research to understand the influence of witnessing a sibling death as a child on subsequent educational and fertility outcomes in Indonesia. Using panel data and a sibling fixed effects model, we identify this relationship based on variation in the age of surviving children within the same family. Our findings strongly support the importance and persistence of adverse childhood experiences. In particular, for surviving sisters, witnessing a sibling death reduces the years of completed education and the likelihood of completing secondary schooling. The effect on surviving brothers is more muted. A potential channel for this result is that women respond by changing their fertility behavior. While surviving the death of a sibling has little effect on desired fertility levels, we find evidence that surviving sisters start a family about 3-4 years earlier. This suggests that interventions targeted at early-life outcomes may have important ripple effects and that the full impact of health interventions may not be visible until decades afterwards
Keywords: I10; J13; J16; O53; 330; Child mortality; Siblings; Education; Fertility